Employee Engagement and Impact on Employee Motivation: A Case Study in Utility Industry, TNB Power Station - D, Mathivaanan; Samsudin, Salmi; Hasnan, Norlena (2019)
Employee engagement has become an essential concept in many organizations. Employee engagement shows how committed or engaged workforce are towards the organizations. In the past, employers don’t give priority to employee engagement. A great deal of interest has been shown in employee engagement in recent years since many research shows that engaged employees are aware of business strategies and company goals and work together with the team to improve individual and team’s performance. Keeping employee engaged is an art of two way communication between employer and employee. Employee engagement helps any organization to recruit and retain skilful and valuable employees, which directly improves company’s business performance and revenues. Therefore, the study interest to explore the engagement factors to the critical industry which have different work environment which could be affected to the business performance. This study is an effort to investigate aspects of employee engagement at the biggest power plant in Malaysia, TNB Janamanjung Sdn. Bhd., and how engagement is associated with employee motivation and how it affects the loyalty of the employee. Qualitative method had been applied, where the framework has been developing accordingly. The results show there are factors in employee engagement to the employee motivation in utility industry